2009
DOI: 10.3899/jrheum.090351
|View full text |Cite
|
Sign up to set email alerts
|

Testing an OMERACT MRI Scoring System for Peripheral Psoriatic Arthritis in Cross-sectional and Longitudinal Settings

Abstract: Further development and testing of the PsAMRIS is planned to improve its performance as a clinical and research tool to identify and measure pathology in peripheral joint PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…The readers had varying degree of MRI experience, but the reliability was overall very good and similar to ICCs from previous OMERACT exercises 36 37. Due to technical difficulties with the anonymisation, we introduced new software prior to the second reading, which may have affected the intrareader reliability.…”
Section: Discussionmentioning
confidence: 52%
“…The readers had varying degree of MRI experience, but the reliability was overall very good and similar to ICCs from previous OMERACT exercises 36 37. Due to technical difficulties with the anonymisation, we introduced new software prior to the second reading, which may have affected the intrareader reliability.…”
Section: Discussionmentioning
confidence: 52%
“…Our own recent study of the MRI features of gout in 47 patients showed bone marrow edema to be present in 36% of those with uncomplicated gout (when it was often mild) but to be almost universal in those with gout complicated by osteomyelitis (when it was usually florid) [19]. In RA, MRI bone marrow edema is related to inflammatory osteitis [5,6]; in osteoarthritis, it is thought to indicate fibrosis and necrosis within subcortical bone [7]. In gout, the pathological correlate of MRI bone marrow edema remains unknown, and further studies are required to elucidate this.…”
Section: Joint Pathology In Goutmentioning
confidence: 99%
“…Scoring systems have been developed to quantify joint inflammation and destruction by using imaging and these are now in routine use in clinical trials to provide sensitive measures of drug efficacy in rheumatoid arthritis (RA) and psoriatic arthritis (PsA) [4,5]. In gout, the applications of advanced imaging are only now starting to be explored and are of particular relevance to the clinician assessing the impact of urate-lowering therapies [6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports emphasize the dominant role of MRI in the diagnosis of arthritis, particularly in the evaluation of synovial inflammation, effusion and erosions [38,39]. However, the role of ultrasound is always noticeable.…”
Section: Discussionmentioning
confidence: 99%